Islamicjerusalem under Muslim rule: a study of the implementation of inclusive vision on the region - Nor, Mohd Roslan Mohd (Dept of Islamic History and Civilization, Academy of Islamic Studies, University of Malaya, Kuala Lumpur, Malaysia, 2008)
This article examines some approaches needed on problems face by Muslims in the context of Islamicjerusalem today. In discussing the related issues, the author tries to present historical facts, the situation of the region and Quranic perspectives on justice as an element to achieve global peace. Apart from that, this article reflects on the future of this disputed region. The author come with the hypothesis "there will be no peace and stability without justice."